Does Portopulmonary Hypertension Impede Liver Transplantation in Cirrhotic Patients? A French Multicentric Retrospective Study. Issue 4 (April 2018) - Reymond, Maud; Barbier, Louise; Salame, Ephrem; Besh, Camille; Dumortier, Jérome; Pageaux, Georges-Philippe; Bureau, Christophe; Dharancy, Sébastien; Vanlemmens, Claire; Abergel, Armand; Woehl Jaegle, Marie-Lorraine; Magro, Pascal; et al.
Abstract : Background: Portopulmonary hypertension is defined by the presence of pulmonary arterial hypertension associated with portal hypertension. Its presence is a major stake for cirrhotic patients requiring liver transplantation (LT), with increased postoperative mortality and unpredictable evolution after transplantation. The aim was to study outcomes after liver transplantation in patients with portopulmonary hypertension and to identify factors associated with normalization of pulmonary hypertension. Methods: Patients with portopulmonary hypertension who underwent LT between 2008 and 2016 in 8 French centers were retrospectively included. Pulmonary artery pressure was established by right heart catheterization before and after LT. Primary endpoint was the normalization of pulmonary artery pressure after LT. Results: Twenty-three patients who received liver transplant between 2008 and 2016 were included. Two (8.7%) patients died in the immediate posttransplant period from right heart failure. With appropriate vasoactive medical treatment and LT, pulmonary arterial pressure was normalized in 14 patients (60.8%), demonstrating recovery from portopulmonary hypertension. In univariate analysis, the use of vasoactive combination therapy was the only prognostic factor for pulmonary arterial hypertension normalization after LT. Conclusions: Treatment of portopulmonary hypertension with a combination of vasoactive drugs allows LT with acceptable postoperative cardiovascular-related mortality and normalization of pulmonary hypertension in the majority of the patients. Abstract : This multicentric French study demonstrates the value of combination vasoactive therapy in liver transplantation for porto-pulmonary hypertension with good results in a well-selected cohort of liver transplantation candidates. Supplemental digital content is available in the text.